Limited human mobility during the Neolithic period in the Meuse and Mons basin in Belgium: multi-element isotopic analysis - IJk van Hattum; Marta Costas-Rodríguez; Kasper Hobin; Prudence Robert; Frank Vanhaecke; Elliot Van Maldegem; Hélène Collet; Pierre Cattelain; Michel Toussaint; Hans Vandendriessche; Samuel Bodé; Pascal Boeckx; et al. (Archaeological and Anthropological Sciences, 2026)
While the introduction of the Neolithic way of life in central Belgium around 5300 BCE is well-documented, the provenance and mobility patterns of Middle to Final Neolithic groups in southern Belgium (Wallonia) remain unclear. This work presents the first multi-element isotopic (strontium, 87 Sr/ 86 Sr; oxygen, δ 18 O; carbon, δ 13 C) data from prehistoric human dental enamel from the region. The study includes a total of 29 individuals, coming from karstic caves in the Meuse basin, the mining complex of Spiennes, and the megalithic tomb of Wéris II. The study also explores the variability of bioavailable strontium ratios in the geologically heterogeneous Meuse basin using modern plants. The analysis of multi-element isotopic data reveals high δ 18 O values and diverse 87 Sr/ 86 Sr ratios. The findings suggest that these individuals likely originated from or spent their childhood in present-day Belgium. Furthermore, the study highlights limited mobility during the Final Neolithic period, characterized by a combination of local residency and potential short-distance mobility or post-mortem movements. Overall, this study provides the first δ 18 O values from ancient human remains in the region and reshapes our understanding of human mobility during the Neolithic in present-day Belgium.